Nanoscale nonlocal thermal transport and thermal field emission in high-current resonant tunnel structures - Michael V. Davidovich; Igor S. Nefedov; Olga E. Glukhova; J. Miguel Rubi (Scientific Reports)
Abstract We present a nonlinear model of thermal field emission in resonant tunneling nanostructures with multiple barriers and potential wells, based on an accurate determination of the quantum potential shape and a rigorous solution of the Schrödinger equation, while considering thermal balance. The model applies to vacuum and semiconductor resonant tunnel diode and triode structures with two and three electrodes and to the general case of two-way tunneling with electrode heating. The complete balance of heat release and transfer is accounted for, with heat transport considered ballistic. This approach can also be extended to the non-stationary case, incorporating the influence of space charge. The short flight time of electrons in such structures makes them promising for the fabrication of THz devices.